Traces of Interaction in Digital Space: On the Tension Between Public Accessibility and Anonymity in Qualitative Research Processes - Bischof, Susann; Lengerer, Franziska; Meyer, Frank (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2022)
Qualitative researchers increasingly use Web 2.0 in various phases of the research process. Both researchers and research participants leave digital traces of their interactions online, often in an unreflective manner. The consequences for anonymity have, however, been only sporadically explored in the literature. With this article, we aim to contribute to the debate on research ethics, data protection, and data management. Based on a fictional case description, we identify three types of interaction traces in digital space: traces of recruitment, traces of public relations work, and traces of participation. These traces can lead to an involuntary and potentially detrimental de-anonymization of participants. By conducting a systematic literature review on anonymity and the use of Web 2.0 in qualitative research, we summarize practical ways of dealing with the identified traces of interaction in digital space and summarize them in a checklist for reflecting on and documenting one's own activities in social media. Our goal is to raise awareness among qualitative researchers about data that is often produced casually online and to encourage an exchange about the diverse decisions that researchers and research participants make when communicating and presenting themselves in Web 2.0.